Pengaruh Gaya Kepemimpinan Situasional Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Koperasi,Usaha Mikro, Kecil Dan Menengah Kabupaten Tolitoli - Hedrat M Nure (Economy Deposit Journal (E-DJ), 2021)
This research is an applied research that aims to find out Situational leadership style and work environment simultaneously and partially that can affect the performance of Cooperatives and micro, small and medium enterprises in Tolitoli Regency. This type of research is a quantitative research with a descriptive verification approach. This study took place in Tolitoli Regency with a focus on the Cooperatives and MSMEs Office, Tolitoli Regency, Central Sulawesi Province. The population in this study were employees of the cooperative and micro, small and medium enterprises office in Tolitoli Regency, totaling 35 employees. The sample was drawn using the saturated sample method, using data acquisition. through observation, questionnaires, and interviews. In the results of data analysis using multiple linear regression, it was found that Situational Leadership Style and work environment simultaneously and partially have a positive effect on the performance of Cooperatives and micro, small and medium enterprises in Tolitoli Regency. Namely, situational leadership style, work environment and good performance at the Tolitoli district cooperative and MSME service. Situational Leadership Style and work environment simultaneously have a positive effect on the performance of the Tolitoli Regency Cooperatives and MSME employees. Situational Leadership Style has a positive effect on the performance of the Tolitoli Regency Cooperatives and MSME employees. The Royal Environment has a positive effect on the performance of the Tolitoli Regency Cooperatives and UMKM Service employees.